The convoluted history of haem biosynthesis - Kořený, Luděk; Oborník, Miroslav; Horáková, Eva; Waller, Ross F; Lukeš, Julius (Biological reviews of the Cambridge Philosophical Society, 2022)
The capacity of haem to transfer electrons, bind diatomic gases, and catalyse various biochemical reactions makes it one of the essential biomolecules on Earth and one that was likely used by the earliest forms of cellular life. Since the description of haem biosynthesis, our understanding of this multi-step pathway has been almost exclusively derived from a handful of model organisms from narrow taxonomic contexts. Recent advances in genome sequencing and functional studies of diverse and previously neglected groups have led to discoveries of alternative routes of haem biosynthesis that deviate from the 'classical' pathway. In this review, we take an evolutionarily broad approach to illuminate the remarkable diversity and adaptability of haem synthesis, from prokaryotes to eukaryotes, showing the range of strategies that organisms employ to obtain and utilise haem. In particular, the complex evolutionary histories of eukaryotes that involve multiple endosymbioses and horizontal gene transfers are reflected in the mosaic origin of numerous metabolic pathways with haem biosynthesis being a striking case. We show how different evolutionary trajectories and distinct life strategies resulted in pronounced tensions and differences in the spatial organisation of the haem biosynthesis pathway, in some cases leading to a complete loss of a haem-synthesis capacity and, rarely, even loss of a requirement for haem altogether.
Keywords: mitochondrion; Biological Evolution; eukaryogenesis; metabolické sítě a dráhy; chloroplast; metabolic pathways; Heme; tetrapyrrole; evolution; Eukaryota; biologická evoluce; hem; photosynthesis; Metabolic Networks and Pathways; porphyrin; iron metabolism